Analisis Teknikal dan Fundamental Terhadap Harga Saham (Studi Kasus pada Saham Perbankan BUMN yang Terdaftar di BEI pada Periode 2019-2024) - Juwita Merinda Tinambunan; Mardaleta Mardaleta; Muzakir Muzakir (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to analyze the influence of technical and fundamental factors on the stock prices of state-owned banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2024 period. The technical variables used include trading volume and stock price volatility, while the fundamental variables consist of Return on Assets (ROA), Return on Equity (ROE), and Earnings Per Share (EPS). The research method used is multiple linear regression with time series data. The results show that technical and fundamental factors simultaneously have a significant effect on stock prices. Partially, trading volume, volatility, ROA, ROE, and EPS have a positive influence on bank stock prices. This research provides an important contribution to investors, banking management, academics, capital market regulators, and the general public in making investment decisions in the state-owned banking sector.